Nucleation and Martensitic Transformation in Subjects of Small Dimensions - Lobodyuk, V.A. (Успехи физики металлов, 2014)
The existing models and schemes of the martensitic phase nucleation are considered in the review. Theoretical and experimental works devoted to the nucleation of the martensitic crystals in different metals are discussed and analysed. The parameters and processes of the martensitic transformation in such subjects of small dimensions as particles, porous materials, thin films, nanoparticles, and nanomaterials are also considered and discussed.